Early histone H4 acetylation during chromatin remodeling in equine spermatogenesis†. Issue 1 (25th November 2017) - Ketchum, Chelsea C; Larsen, Casey D; McNeil, Alexis; Meyer-Ficca, Mirella L; Meyer, Ralph G
Abstract: Chromatin remodeling during spermatogenesis culminates in the exchange of nucleosomes for transition proteins and protamines as an important part of spermatid development to give rise to healthy sperm. Comparative immunofluorescence analyses of equine and murine testis histological sections were used to characterize nucleoprotein exchange in the stallion. Histone H4 hyperacetylation is considered a key event of histone removal during the nucleoprotein transition to a protamine-based sperm chromatin structure. In the stallion, but not the mouse, H4 was already highly acetylated in lysine residues K5, K8, and K12 in round spermatids almost immediately after meiotic division. Time courses of transition protein 1 (TP1), protamine 1, H2A histone family member Z (H2AFZ), and testis-specific histone H2B variant (TH2B) expression in stallion spermatogenesis were similar to the mouse where protamine 1 and TP1 were only expressed in elongating spermatids much later in spermatid development. The additional acetylation of H4 in K16 position (H4K16ac) was detected during a brief phase of spermatid elongation in both species, concomitant with the phosphorylation of the noncanonical histone variant H2AFX resulting from DNA strand break-mediated DNA relaxation. The results suggest that H4K16 acetylation, which is dependent on DNA damage signaling, may be more important for nucleosome replacement in spermiogenesis than indicated by data obtained in rodents and highlight the value of the stallion as an alternative animal model for investigating human spermatogenesis. A revised classification system of the equine spermatogenic cycle for simplified comparison with the mouse is proposed to this end. Summary Sentence: Histone H4 acetylation marks that are necessary for nucleosome removal appear immediately after meiosis in equine but not murine spermatids.